Legal Analysis of Legal Protection for Doctors in Reporting Patient Safety Incidents to Improve the Quality of Health Services - Bintartho, Agung; Nasser, M; Sutrisno (KRTHA BHAYANGKARA, 2025)
Study This give deep insight about protection law for doctor in practice medical based on Constitution Number 17 of 2023 concerning Health and its derivatives . Focus main study This is For highlight challenges and dilemmas faced by doctors in operate his profession , including problem protection law for doctor in report incident safety patients , with hope can increase quality service health in a way overall , which at the moment This Still referring to the Minister of Health Regulation no. 11 of 2017 concerning safety patient . One of the the most crucial aspect in study This is analysis to Article 189 of the Health Law , which regulates importance effective communication between House sick and patient . Article This underline obligation doctors and institutions health For build transparent , clear , and interest - oriented communication patient . In context this , good communication can reduce potential misunderstanding and avoidance problem the law that arises consequence lack of information or ambiguity in service medical . Besides that , service model health offered by the Law This put forward not quite enough answer together between provider service health and patients . In matter This , Article 310 emphasizes that the patient also has obligation For active participate in the treatment process , providing the necessary information , as well as follow instructions medical with well , as part from safety patient . Responsibility answer together This No only aim For protect profession medical from potential demands law , but also creates environment service more optimal health , where both , doctor and patient , can each other support For reach the best results . Through study this , it is hoped There is improvement quality communication in practice medicine and more Lots understanding about regulated rights and obligations in The Health Law , which finally can repair connection between doctors and patients , as well as increase quality service health in a way overall